Health – seeking behaviour of rural dwellers for the treatment of presumptive malaria in North-Western Nigeria - Abdulrazaq Abdullahi Gobir; Mohammad Nasir Sambo; Suleman Idris Hadejia (penerbit ukm, 2014)
Malaria is endemic throughout Nigeria. Majority of Nigerians, 70%, live in rural areas where subsistence farming is the main occupation. Most of them live below poverty line, earning less than USD1.25 a day. Their health-seeking behaviour for treatment of malaria is infl uenced by their low socioeconomic status since cost of treating malaria varies according to type of drug prescribed and source of treatment. This cross-sectional descriptive study was conducted to assess the health-seeking behaviour of rural dwellers for treatment of presumptive malaria in Gimba village, a rural community of Kaduna State, Nigeria. It was conducted during Community Diagnosis posting of trained fi nal year medical students of Ahmadu Bello University, Nigeria, in July 2012. An interviewer-administered questionnaire was used to collect data from all households in the community. Data analysis was done using STATA (Version 11. Stata Corporation 2009). Most of the respondents were farmers (69.7%). The category of household members that were most affected by malaria (presumptive) were under fi ves (47.4%) followed by housewives (26.5%). Majority of the households (73%) treated their last episodes of presumptive malaria at private drug vendor shops. There was a statistically signifi cant association between cost of treatment and place of seeking treatment (p < 0.001).The result indicated that most rural dwellers patronise unprofessional drug vendors for cheaper treatment of presumptive malaria. This jeopardizes malaria control efforts. For successful malaria control, it is recommended that the treatment of malaria should be free or subsidized and policies that favour Rural Economic Development should be implemented.